Failure to Fulfill Children's Educational Rights as a Violation of the Law in the Context of Parents' Economic Incapacity - Kesuma, Denny Chen Indra Nata; Hasibuan, Ali Huristak Hartawan; Setyawan , David Novan (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2026)
This research offers novelty by positioning children's educational rights not only as social and economic rights, but also as an integral part of children's civil rights that have legal consequences for those who are obliged to fulfill them. The purpose of this study is to examine the fulfillment of children's educational rights as part of civil rights in the context of parents' economic incapacity. The method used is normative legal research with a legislative approach and a conceptual approach, through the study of various legal provisions that regulate children's educational rights. The results of the study show that the failure to fulfill children's educational rights due to parents' economic limitations is not solely a social problem, but also a legal issue related to the protection of children's civil rights. From the perspective of civil law, parents have a legal obligation to fulfill the child's educational rights as part of the civil responsibility inherent in the relationship between parents and children. However, this responsibility cannot be fully imposed on parents, but also involves the role of the state in ensuring the fulfillment of children's educational rights. The practical implication of this study is the need to strengthen the role of the state through more effective policies and legal instruments in ensuring access to education for children, especially those from economically disadvantaged families, as well as the affirmation of legal responsibility mechanisms for parties who are negligent in fulfilling these rights.